Comparison of antinuclear antibody testing methods: immunofluorescence assay versus enzyme immunoassay. - Gniewek, R A (1997)
Performances of anti-nuclear antibody testing by immunofluorescence assay (ANA-IFA) and enzyme immunoassay (ANA-EIA) were compared in relation to patient diagnosis. A total of 467 patient serum samples were tested by ANA-IFA (Kallestad; Sanofi) and ANA-EIA (RADIAS; Bio-Rad), and their age, sex, diagnosis, disease status, and medications were obtained through chart review. Reference ranges were established by testing 98 healthy blood donor samples. Eighty-six samples came from patients with diffuse connective tissue diseases, including systemic lupus erythematosus, discoid lupus erythematosus, or drug-induced lupus (n = 71); systemic sclerosis, CREST syndrome (calcinosis, Raynaud's phenomenon, esophageal motility abnormalities, sclerodactyly, and telangiectasia), or Raynaud's syndrome (n = 8); Sjögren's syndrome (n = 5); mixed connective tissue disease (n = 5); and polymyositis or dermatomyositis (n = 3). The sensitivity, specificity, positive predictive value, and negative predictive value for ANA-IFA were 87.2, 48.0, 29.1, and 93.9%, respectively, for the reference range of < 1:160. For ANA-EIA, they were 90.7, 60.2, 35.8, and 96.4%, respectively, for the reference range of < 0.9. ANA-EIA offers equivalent sensitivity and higher specificity compared to ANA-IFA.